To determine which student's solution is incorrect, let's examine both Jamal's and George's work step by step.
Original Equation:
The original equation given is: \[ x^2 + 4x - 5 = 7 \]
Step 1 for Both: Set Equation to 0
Both students need to rearrange the equation to have it equal to zero. This means moving 7 to the left side: \[ x^2 + 4x - 5 - 7 = 0 \] This simplifies to: \[ x^2 + 4x - 12 = 0 \]
Jamal's Step 1 is correct.
Now for George's Step 1, he incorrectly stated: \[ x^2 + 4x - 5 = 7 \] and did not set it to 0 correctly.
Analysis of Steps:
-
Jamal correctly wrote the equation as: \[ x^2 + 4x - 12 = 0 \]
-
George did not set the equation to zero correctly and continued from his incorrect equation.
Step 2: Factoring
Now let's see their factorization.
-
Jamal's Factorization: He factored \( x^2 + 4x - 12 \): \[ (x + 6)(x - 2) = 0 \]
To confirm:
- The factors of -12 that add up to 4 are indeed 6 and -2.
-
George's Factorization: He stated: \[ (x + 5)(x - 1) = 7 \] This is inherently incorrect since it does not represent a correct factorization of the original equation. The left-hand side was supposed to be 0.
Step 3: Setting Factors to Zero
-
Jamal set his factors correctly as: \[ x + 6 = 0 \quad \text{and} \quad x - 2 = 0 \]
From these, he correctly found the solutions: \[ x = -6 \quad \text{and} \quad x = 2 \]
-
George's step does not apply since his factors (incorrectly set to equal 7) were based on the wrong equation.
Conclusion:
Jamal is correct in his solving of the quadratic equation. He ended up with correct solutions of \( x = -6 \) and \( x = 2 \).
George is incorrect; he did not rearrange the original equation properly in Step 1, leading to incorrect factorization and incorrect solutions. Therefore, his method is inaccurate from the very beginning.